Kiai Charismatic Leadership in Developing The Mamba'ul Ma'arif Denanyar Islamic Boarding School - Sulthon Sulaiman; Achmad Patoni; Ngainun Naim; Ahmad Supriyadi (Publisher Cv. Inara, 2024)
This research departs from the development of Islamic boarding schools as educational institutions able to maintain their existence in the dynamics of global education. The dynamization and stabilization of Islamic boarding schools as one of the leading education systems in Indonesia is indeed inseparable from the leadership carried out by the caregivers and managers of Islamic boarding schools. This research took the locus at Yayasan Pondok Pesantren Mambaul Maarif Denanyar Jombang East Java to find answers to the following questions; How is the leadership of kiai concerning policy making for the development of Islamic boarding schools in the Mamba'ul Ma'arif Denanyar Jombang Islamic Boarding School; How is the kiai program program in the development of Islamic boarding schools in the Mamba'ul Ma'arif Islamic Boarding School Denanyar Jombang; How is the development of kiai in the development of Islamic boarding schools in the Mamba'ul Ma'arif Islamic Boarding School Denanyar Jombang. This qualitative research uses a phenomenological approach using a single case design. The research location is Pondok Pesantren Mambaul Maarif Denanyar Jombang, East Java. Data collection techniques use observation, interview and documentation techniques. Data analysis includes single-case analysis and cross-case analysis with data reduction analysis techniques, data presentation and conclusions. The results showed that; Policy making is carried out through; charismatic leadership model approach in policy setting; application of a democratic-consultative collective-collegial leadership system in policy formulation; policy making based on deliberation, and; laughter and spiritual based; The development program includes; development of Islamic boarding school academic programs in the form of shawir activities and peer reading; improvement of pesantren facilities; economic development; the Jalin Alumni program, and; sincerity-based Coaching is carried out through mechanisms; periodic coaching; emphasis on discipline; self-reliance briefing; suppression of civilized behavior; supervision and guidance based on guardians and alumni, and; based on laughter